STUDENTS’ ANXIETY AND SPEAKING ABILITY: CORRELATIONAL STUDY OF EFL CLASSROOM - AINI, NURUL; Ary Setya Budhi Ningrum (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2023)
The aim of this study was to find out the relationship between a student's anxiety and their ability to speak. The research design used in this study was quantitative. The population of this study were the second grades students of SMK Pawyatan Daha 1 Kediri. A total of 80 students were chosen as the sample. The data was collected using two instruments: the first was questionare to assess students' anxiety in learning English as a foreign language by using the Foreign Language Classroom Anxiety Scale (FLCAS) developed by Howirtz, and the second was a speaking test to assess students' speaking ability. The researcher used Pearson product moment to analyze the data. The basis for decision making, if the significance value (sig.) is less than 0.05 then there is a relationship between the two variables. From the data result it can be seen that the significance value indicates 0.777 (0,777 > 0,05). The value of R count is 0,032. This is obviously lower than the r-table (level of significance (5% or 0.05, n= 80) so the r table is 0,220. It automatically indicates that H0 is accepted. It can be concluded that there is no a significant relationship between the two variables.